Ultra-fine dark matter structure in the solar neighbourhood - Fantin, Daniele S.M. (2011)
Dark matter plays a fundamental role in theories of the formation and evolution of galaxies. Thus every attempt to model galaxy formation and evolution has to take into consideration the presence of dark halos. Moreover, mergers and accretion appear to be fundamental driving mechanisms in determining the present day properties of galaxies. The aim of this thesis is to study the ultra-fine distribution of dark matter in the Solar neighbourhood, and to investigate the implications for the current and next generation of dark matter directional detectors. For this purpose we develop a model for halo mergers in a Milky Way-like galaxy. The signals expected in lab-based dark matter detection experiments depend on the phase-space distribution on sub-milliparsec scales. With our numerical technique it is possible to resolve structures produced by minor mergers of subhalos with a larger parent halo. This type of substructure is unaccessible to conventional N-body simulations. When applied in a cosmological context,this method becomes a powerful instrument to reproduce and analyse the complete multiple merger history of a Milky Way-like system. The results obtained simulating the Galactic halo suggest that the velocity distribution in the solar neighbourhood after an evolution time corresponding to the lifetime of our galaxy (≃ 14Gyr) is smooth. This result suggests the presence of a huge number of dark matter streams that overlap to form a smooth distribution. Nevertheless, the final velocity distribution has overdensities for all the cases that has been analysed. They are generated by a very large number of merger events, but the current generation of detectors have not the angular resolution required to observe these features. A future generation of detectors with a resolution of ~ 1◦ would start to resolve them, allowing the merger history of the Galaxy to begin to be unravelled using this diagnostic.